RAHASIA AMTSAL DALAM AL-QUR’AN: (Kajian Etnografi Aktualisasi Manusia Berkualitas Berdasarkan Q.S. Ibrahim 24-25) - Dudung Abdul Karim; Nurcahyati Nurcahyati; Abdur Rokhim Hasan; Nur Muhammad Iskandar (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
The Qur'an is the word of Allah SWT which contains many miracles, both in terms of meaning and language. One aspect of the beauty of its language lies in the use of metaphors or proverbs. Amtsal is a form of comparison that describes an expression by equating it with another expression because of similarities. Therefore, this paper discusses the Secret of Proverbs in the Qur'an, focusing on: 1) Definition, history, and characteristics of Qur'anic Proverbs; 2) Types of Qur'anic Proverbs; and 3) Benefits and wisdom of Qur'anic Proverbs; 4) Ethnography regarding the actualization of human quality in the verse of proverbs. This research uses a qualitative approach with Library Research as a data collection technique. Qur'anic Proverbs is a method used in the Qur'an to describe something abstract to become real. The characteristics of proverbs involve similarities between two objects, concretizing something abstract, and explaining vague properties or circumstances. Proverbs are divided into three types, namely musharahah proverbs, kaminah proverbs, and mursalah proverbs. Proverbs can also reflect the ethnography of the actualization of quality human beings, as illustrated in the parable of Allah SWT in Q.S. Ibrahim: 24-25, which shows that good speech (Tayyibah) is an indicator of human quality.